Accelerated Lifetime Tests for SOFCs. (2nd June 2015) - Weber, André; Szász, Julian; Dierickx, Sebastian; Endler-Schuck, Cornelia; Ivers-Tiffée, Ellen
Abstract : Conventional lifetime analysis for Solid Oxide Fuel Cells requires considerable testing time and capacities. In case of application oriented testing durations of several years the results can not be used for the continued development of cells and stacks before the test is finished. Therefore accelerated lifetime tests, which enable a rapid degradation analysis, would be highly desirable. In this paper we will show that the overall degradation rate of a single cell can hardly be used in accelerated lifetime tests. It is required to evaluate the degradation of the electrochemical processes in each cell component. The degradation of cathode, electrolyte and anode was deconvoluted by (i) impedance spectroscopy, (ii) distribution of relaxation times data analysis and (iii) a subsequent CNLS-Fit. Such approach can provide stress level dependencies for the aging of individual electrochemical processes in the cell.